2013
DOI: 10.1161/circep.113.000170
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Implantable Cardioverter Defibrillators in Young Patients With Catecholaminergic Polymorphic Ventricular Tachycardia

Abstract: Background— The effectiveness of implantable cardioverter-defibrillator (ICD) therapy for the management of catecholaminergic polymorphic ventricular tachycardia (VT) in young patients is not known. ICD discharges are not always effective and inappropriate discharges are common, both resulting in morbidity and mortality. Methods and Results— This is a multicenter, retrospective review of young patients with catecholaminergic polymorphic V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(78 citation statements)
references
References 26 publications
2
76
0
Order By: Relevance
“…Careful ICD programming is necessary in CPVT because the effectiveness of appropriate shocks critically depends on the arrhythmia mechanism, usually being effective only when the treated rhythm is ventricular fibrillation. 31,32 Thus, CPVT patients with arrhythmic events despite β-blockers are in dire need of an effective adjunct therapy. The present data conclusively indicate that LCSD represents a viable and effective answer to this predicament.…”
Section: Discussionmentioning
confidence: 99%
“…Careful ICD programming is necessary in CPVT because the effectiveness of appropriate shocks critically depends on the arrhythmia mechanism, usually being effective only when the treated rhythm is ventricular fibrillation. 31,32 Thus, CPVT patients with arrhythmic events despite β-blockers are in dire need of an effective adjunct therapy. The present data conclusively indicate that LCSD represents a viable and effective answer to this predicament.…”
Section: Discussionmentioning
confidence: 99%
“…1,12,14,16 Some recent studies have suggested that ICD may be harmful to CPVT patients, however, because both appropriate and inappropriate ICD shocks can potentially induce VT storms and cardiac arrest. 16,17 Therefore, ICD implantation should be restricted to patients with symptoms refractory to optimised medical treatment and LCSD. 18 …”
Section: Discussionmentioning
confidence: 99%
“…7,8 Although ICDs may prevent sudden death in some cases, there are case reports of ICD discharges being proarrhythmic in CPVT and the high voltage function does nothing to prevent arrhythmia from occurring in the first place. 9 For clinicians, LCSD is an appealing approach: its efficacy is independent of patient compliance and it avoids the pulmonary side effects of β-blockers.…”
Section: Article See P 1151mentioning
confidence: 99%